Situational and organizational influences on transparency following financial restatements - A. J. Guerber; Vikas Anand (Cogent Business & Management, 2019)
This study explores the influence of situational and organizational factors on transparency regarding financial restatements. It is predicted that situational factors related to the severity of a restatement will influence transparency about the event and that an organization's stakeholder orientation will moderate the relationship between the magnitude of the restatement and transparency. Consistent with predictions, results show a generally positive relationship between the severity of the restatement and transparency in the restatement announcement but also show that firm characteristics such as size, profitability, and stakeholder orientation can alter this relationship. Although transparency following restatements is generally viewed as desirable, we find that among smaller firms transparency is negatively related to the severity of the restatement, and we theorize that this is due to risk aversion triggered by fears that the firm may fail as a result of the restatement. We also find that companies with an individualistic identity orientation alter their transparency following a restatement depending on the severity of the restatement whereas firms which derive organizational identity from relationships with stakeholders or broader groups display a more consistent level of transparency across restatements of varying severity. Taken together, the results of this study provide increased understanding of factors which influence transparency following restatements and suggest that increased attention should be given to the role of organizational characteristics in shaping responses to such events.
Keywords: 650; transparency; stakeholder orientation; organizational identity orientation; financial restatements; corporate communications; corporate social performance